THE CONNECTION BETWEEN STUDENTS' READING COMPREHENSION AND READING CONCERN IN AN ESP CONTEXT (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This paper investigates the intricate relationship between reading comprehension and reading concern among students in an English for Specific Purposes (ESP) context. While reading comprehension is a well-researched area, the affective dimension of "reading concern"—encompassing anxiety, apprehension, and reluctance related to reading tasks—is often overlooked, particularly in specialized language learning environments. This study aims to explore the extent to which reading concern influences reading comprehension, and vice-versa, among ESP learners who encounter discipline-specific texts. Employing a mixed-methods approach, data was collected through a standardized reading comprehension test, a reading concern questionnaire, and semi-structured interviews. Preliminary findings suggest a significant negative correlation between high levels of reading concern and lower reading comprehension scores. Furthermore, qualitative data illuminate specific factors contributing to reading concern within the ESP context, such as unfamiliarity with technical jargon, perceived pressure to perform, and a lack of confidence in domain-specific knowledge. The study concludes by offering pedagogical implications for ESP instructors to mitigate reading concern and enhance reading comprehension.